2008
DOI: 10.1002/aic.11436
|View full text |Cite
|
Sign up to set email alerts
|

A new solventless process to hydrophobize silica powders in fluidized beds

Abstract: A new hydrophiztaion technique was developed in a fluidized bed reactor to modify the surface of silica‐based powders with n‐octadecyltrichlorosilane (ODTCS). The reaction was performed at dry phase by mixing two classes of particles during the fluidization: “target‐particles” to be treated (a fine microporous silica powder) and “ODTCS‐carrier” particles consisting of coarser porous alumina beads containing an adequate amount of reagent. The results showed that ODTCS was successfully anchored on silica surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The latter strategy (sometimes called grafting) is used in this study. Two silylation mechanisms have been proposed. , The first is the widely accepted sol−gel mechanism, in which moisture (either added or adsorbed to silica particles stored under atmospheric conditions) hydrolyzes the chloro- or alkoxy-leaving groups of the silane, followed by condensation with surface silanol groups. , One recent study has shown that it is even possible to exploit this mechanism in a solventless silylation process. The second mechanism that has been proposed is a direct one-step nucleophilic substitution mechanism believed to sometimes operate during vapor phase silylation in a dry atmosphere …”
Section: Introductionmentioning
confidence: 99%
“…The latter strategy (sometimes called grafting) is used in this study. Two silylation mechanisms have been proposed. , The first is the widely accepted sol−gel mechanism, in which moisture (either added or adsorbed to silica particles stored under atmospheric conditions) hydrolyzes the chloro- or alkoxy-leaving groups of the silane, followed by condensation with surface silanol groups. , One recent study has shown that it is even possible to exploit this mechanism in a solventless silylation process. The second mechanism that has been proposed is a direct one-step nucleophilic substitution mechanism believed to sometimes operate during vapor phase silylation in a dry atmosphere …”
Section: Introductionmentioning
confidence: 99%
“…Elimination of the physisorbed water molecules and deposition of self-saturating molecular layers of alkoxysilanes can be most easily performed in the gas phase. Different silane layers have been deposited onto silica powders in the gas phase by means of carrier particles containing a known quantity of modifying agent. , However, this approach does not provide control over the thickness and morphology of the deposited layer. Aminosilane layers have been deposited onto silicon dioxide substrates in gas phase via atomic layer deposition (ALD) .…”
Section: Introductionmentioning
confidence: 99%
“…The dominant functional groups of the silica surfaces are siloxane (Si-O-Si) and silanol (-Si-OH) groups, which render these materials highly hygroscopic, and the presence of surface silanol groups also implies functionality to allow the better control of drug loading and release [12][13][14]. By functionalizing the surface, the new functional groups can develop strong interactions, which may lead to drug release retardation [15][16][17]. However, in an utterly different approach, the contribution of attractive drug-surface interactions is not necessarily increased, but the hydrophilicity of the silica carrier is decreased.…”
Section: Introductionmentioning
confidence: 99%